Combate del gorgojo del camote Rhyssomatus near subcostatus (Fabr) - Viale, E.; Thomas, N. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A new comparative field test was conducted by the Inter-American Institute of Agricultural Sciences on control of a sweet-potato weevil of the genus Rhyssematus. The four insecticides tested were applied to the surface of the soil and disked in just before the ridges were made for the sweet-potato cuttings. Three formulations, emulsion, suspension, and dust, were used at three different rates, 25, 40, and 55 gr. per 100 sq m. soil surface. Dieldrin gave the best results as expressed in the least infestation and the highest marketable yield. The increase of the latter for the treated plots over the untreated was above 560 per cent. Aldrin was second best; emulsion showed a better control than wettable powder (450 vs. 255 per cent over the check yields). The average marketable yield for lindane was 310 per cent over the check. Chlordane suspensions gave a low degree of control; the emulsion form, however, showed a higher degree of control. The experimental results obtained on the control of this sweet-potato weevil were supplemented by vestigial-winged Drosophila fly bio-assays. All the samples so analyzed, including the various Dieldrin, Aldrin, and Lindane treatments, showed fly mortality rates below that of the lower standard level of 0.1 ppm of the chemical involved.